Digital Marketing as a Mediating Mechanism Between Service Quality and Price: An Applied Study on Patient Satisfaction - Rusno; Iva Nurdiana (Global Research and Collaboration, 2026)
This study examines service quality and price perception affect patient satisfaction, and it investigates how digital marketing in healthcare services acts as a mediator. Increasing competition in the healthcare sector requires hospitals to improve service performance while adopting digital communication strategies to enhance patient satisfaction. This research employs a quantitative explanatory approach using survey data collected from patients at RS Mitra Delima, Malang Regency. A total of 218 respondents werechosen through proportional random sampling. Data collection involved structured questionnaires, which were assessed using a five-point Likert scale and analyzed using WarpPLS 8.0 to evaluate both the measurement model and the structural relationships among variables. The results indicate that service quality and price perception have significant positive effects on patient satisfaction. Digital marketing also significantly influences patient satisfaction and acts as a mediating variable that strengthens the relationship between service quality, price perception, and patient satisfaction. This study highlights the strategic role of digital marketing as a mechanism that enhances the impact of service quality and pricing strategies on patient satisfaction. The findings provide practical implications for healthcare institutions to integrate service excellence, transparent pricing, and effective digital marketing in improving patient satisfaction and competitiveness.